Analisis Kebutuhan Mesin Pemanen Padi (Combine Harvester) Menggunakan Sistem Informasi Geografis di Kabupaten Pringsewu - Satria, Achmad; Ridwan, Ridwan; Suharyatun, Siti; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2024)
Agricultural mechanization has developed in Indonesia. This can be seen from shift of farmers from conventional farming to mechanical farming. Agricultural mechanization aims to ease human labor in agricultural production. The use of agricultural machinery, such as Combine Harvester, can improve farming efficiency. This study aims to analyse land suitability for the use of Combine Harvester and demand of Combine Harvester in Pringsewu Regency. This study uses non-spatial and spatial data. The non-spatial data consisting of: (a) number of Combine Harvesters available, (b) Combine work capacity Harvester, (c) Combine Harvester working hours and, (d) number of Combine Harvester working days. The Spatial data includes: (a) paddy field maps, (b) rainfall maps, (c) slope maps, and (d) soil type maps. The suitability level for the application Combine Harvester in Pringsewu Regency was obtained through an overlaying of map that are limiting factor, including rainfall maps, slope maps, and soil type maps. The analysis result show that the area of harvested paddy field using Combine Harvester in Pringsewu Regency covers 1,330.75 ha, or 11.35% of the total paddy field area. Meanwhile, the area of harvested paddy field not using Combine Harvester covers 10,311.14 ha, or 88.66% of the total paddy field area Ttotal demand for Combine Harvester in Pringsewu Regency is 580 units, consisting of 7 unit small unit, 570 mediums unit and 3 large units. Keywords: Combine Harvester, Mechanization, Non Spatial, Physical Conditions of the Area, Spatial.